Postbariatric Brachioplasty with Posteromedial Scar: Physical Model, Technical Refinements, and Clinical Outcomes. Issue 2 (February 2018) - Simone, Pierfranco; Carusi, Carlo; Segreto, Francesco; Iannuzzi, Riccardo; Buscaglione, Silvia; Gizzi, Alessio; Giannitelli, Sara; Rainer, Alberto; Filippi, Simonetta; Persichetti, Paolo
Abstract : Background: Brachioplasty is an increasingly performed procedure following massive weight loss. A visible scar is the main hindrance to this surgery. The aims of the study were to develop a physical model to investigate the ideal location of the surgical incision and to present the authors' technical refinements with the posteromedial scar approach. Methods: Twenty-four postbariatric patients underwent brachioplasty with posteromedial scar placement, concomitant liposuction, fascial plication, and axillary Z-plasty. Skin specimens were tested and a physical model of the arm was set up to investigate the difference in mechanical stress on the posteromedial and medial scars. The validated Patient and Observer Scar Assessment Scale, the Vancouver Scar Scale, and a questionnaire assessing subjective improvements were administered to patients. Preoperative and postoperative photographs were assessed by three independent plastic surgeons. Results: The physical model showed that stress intensity and distribution along the scar were reduced in the posteromedial location, with smaller scar displacement in the loading simulations. Twenty-three patients healed uneventfully. One (4.1 percent) had a 2-cm dehiscence. Mean Patient and Observer Scar Assessment Scale scores were, respectively, 2 ± 0.76 and 2.13 ± 0.64 in the patients' and observers' questionnaires. The mean Vancouver Scar Scale value was 3.5 ± 1.7. Questionnaires assessing the subjective outcomes showed a mean value of 3.45 ± 0.63 of 4. The surgeons' assessment resulted in a score of 4.5 ± 0.4 of 5. Conclusions: The physical model demonstrated that the posteromedial scar was subjected to lower mechanical stress and displacement. The reported technical refinements allowed pleasant arm recontouring to be achieved with acceptable scarring and a low incidence of complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.This and Related "Classic" Articles Appear on PRSJournal.com for Journal Club Discussions.